2022
DOI: 10.1111/ijfs.16256
|View full text |Cite
|
Sign up to set email alerts
|

Study on antioxidant activity of wheat bran extract microcapsules in vitro and in vivo

Abstract: Wheat bran extracts (WBE, mainly composed of feruloyl oligosaccharides (FOs)) have been approved by FDA in GRAS Notice. WBE was utilised in octenyl succinate anhydride-modified starch (OSA-starch)based microcapsules as wall materials to protect β-carotene (BC) from oxygen. The storage retention and antioxidant indexes in vivo and in vitro of microcapsules were determined. The results showed that these characteristics were positively related to the proportion of WBE in the wall material. The in vivo antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Sibhatu et al employed the same approach for ferulic acid production and got 46.17 mg FA per 100 g of brewery spent grains (Sibhatu et al, 2021). Gong et al and Yu et al adopted the same method for the quantification of FA content in wheat bran FOs prepared by enzyme-assisted extraction and the FA content were 39.24 and 41.25 mg/g, respectively (Gong et al, 2019;Yu et al, 2022). Therefore, it demonstrated that HPLC could be used to quantify FA content in FOs at first.…”
Section: Spectral Analysis Results Of Purified Wheat Bran Fosmentioning
confidence: 99%
See 3 more Smart Citations
“…Sibhatu et al employed the same approach for ferulic acid production and got 46.17 mg FA per 100 g of brewery spent grains (Sibhatu et al, 2021). Gong et al and Yu et al adopted the same method for the quantification of FA content in wheat bran FOs prepared by enzyme-assisted extraction and the FA content were 39.24 and 41.25 mg/g, respectively (Gong et al, 2019;Yu et al, 2022). Therefore, it demonstrated that HPLC could be used to quantify FA content in FOs at first.…”
Section: Spectral Analysis Results Of Purified Wheat Bran Fosmentioning
confidence: 99%
“…The FTIR findings revealed the formation of ester bonds between ferulic acid and saccharides. The distinctive FTIR profile of wheat bran FOs, achieved through B. amyloliquefaciens IT‐45 fermentation, exhibited similarities to the profile of wheat bran‐derived FOs by Aspergillus niger fermentation (Yu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations